The chatbot as a communicative, marketing and business success factor: empirical analysis - Fondevila Gascón, Joan Francesc (2024)
This research explores the perception of customers in Spain about interactions with chatbots as customer service agents and attempts to identify the communicative and marketing factors of success in this interactivity, which is growing in the Broadband Society. To achieve the research objectives, a quantitative methodology is followed through a survey aimed at Spanish clients without distinction of origin. The results show that customers’ perception of the chatbot depends on the context. If the customer’s question or request is simple, the perception is positive; if it is a complex question, the perception is negative. Furthermore, it is observed that the main factors that affect customer perception are quality and context. It is concluded that there is a relationship between the quality of the chatbot and customer satisfaction and it has been identified that the most important factor for the consumer when interacting with a chatbot is effectiveness.